EMERGING CHALLENGES IN IMPLEMENTING UNIVERSAL HEALTH COVERAGE DUE TO COVID-19 IN INDONESIA - Rosyidah Rosyidah (Epidemiology and Society Health Review (ESHR), 2022)
The goal of Universal Health Coverage (UHC) means a situation in which all individuals and communities have access to health services, whenever and wherever they need them, without financial barriers to obtaining them. UHC covers a wide range of essential health services, from promotion, prevention, treatment, care, rehabilitation, and palliative care for patients with chronic diseases. On the other hand, the COVID-19 Pandemic is devastating national health systems in countries that have strived to provide UHC, hampering their efforts to fulfill the ethos of universal health coverage, which is to "leave no one behind." As mentioned in the World Economic Forum 2021, this issue is interesting because an estimated 400 million people worldwide lack access to essential health services. Approximately 100 million people fall into poverty each year due to not paying their health costs. This number has increased with COVID-19 and will continue to up as people lose their jobs, health insurance, and health spending rise due to COVID-19-related spending on testing, treatment, and vaccines.